Model senam lansia untuk kebugaran jasmani dan fungsi otak - Putra, Edo Fralian; Suharjana, Suharjana (Jurnal Keolahragaan, 2018)
Penelitian ini bertujuan untuk menghasilkan sebuah senam lansia untuk kebugaran jasmani dan fungsi otak. Metode penelitian ini mengacu pada penelitian Borg & Gall dengan tahapan: studi pendahuluan, analisis desain draf awal, validasi ahli, uji coba produk, evaluasi, dan revisi. Subjek uji coba skala kecil 15 orang, subjek uji coba penelitian skala besar 57 orang, dan subjek uji efektifitas produk 12 orang. Penilaian para ahli dan instruktur menggunakan kuisioner. Pengukuran kebugaran jasmani lansia menggunakan tes uji jalan 6 menit, sedangkan untuk mengukur fungsi kognitif lansia menggunakan tes The Montreal Cognitif Assesment  Indonesia (MoCA–Ina). Hasil penelitian menunjukkan, model senam lansia valid, serta layak dan efektif untuk kebugaran jasmani dan fungsi otak. Hasil validasi ahli kesehatan lansia dan akademisi sekaligus praktisi kesehatan termasuk "sangat baik" dengan rata-rata 81,87%. Kualitas produk hasil uji coba skala kecil "sangat baik" dengan rata-rata 86,25. Uji coba skala besar juga termasuk "sangat baik" dengan rata-rata 98,12%. Hasil uji efektifitas produk menunjukkan peningkatan kebugaran jasmani lansia 0,32 poin (hasil pretest 4,4092 dan hasil postest 4,7292). Hasil uji efektifitas menunjukkan peningkatan fungsi kognitif lansia dengan 1,72 poin, (hasil pretest 25,58 dan hasil posttest 27,33). A gymnastic older model for pphysical fitness and brain function AbstractThis study aimed to develop an elderly gymnastics model for physical fitness and brain function. This research was research and development  which refered to Borg & Gall's research steps through preliminary study, initial draft design analysis, expert validation, product trial, evaluation, and revision. The subjects of the small-scale trial were 15 people, the subjects of the large-scale trials were 57 people, and the subjects of the product effectiveness test were 12 people. The assessment of experts and instructors used a questionnaire sheet. The measurement of elderly physical fitness used a 6-minute walk test, while measuring their cognitive function used the Montreal Cognitive Assessment Indonesia (MoCA-Ina) test. The results showed that  the developed elderly gymnastics model for physical fitness and brain function was valid. The result of expert validation showed the model was "very good" with an average  score of 81.87%. The quality of the product according to the small-scale test was "excellent" with an average score of 86.25%. Furthermore, based on the large-scale trials the product was "excellent" with an average score of 98.12%. The results of the effectiveness test showed an increase in physical fitness of the elderly by  0.32 points (the pretest score of 4.4092 to the result of postest score of 4.7292). The result of the effectiveness test showed improvement of cognitive function of elderly by 1,72 point (the pretest score of 25.58 to the result of posttest score of 27.33).